A glimpse of the developmental pathway to elite level swimming - a multidimensional and longitudinal analysis of youth swimmers - Post, A. K.; Koning, R. H.; Visscher, C.; Elferink-Gemser, M. T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: A thorough understanding of performance development and its underlying performance characteristics during an swimmers` career could facilitate the identification and development of talented swimmers. However, longitudinal studies on multidimensional performance characteristics in talented youth swimmers are scarce. Therefore, the aim of the present study is examine the development of anthropometric, physiological, technical and psychological characteristics in relation to performance level of talented youth swimmers over a 3-year period.